Sosialisasi Penerapan Prinsip Pengelolaan BUMDES di Desa Taman, Kec. Jrengik, Kab. Sampang - Siti Aisyah; Sumriyah Sumriyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The existence of Village-Owned Enterprises or called VOE in improving the village economy has not fully carried out its role. Considering its legality as a legal entity, it is important to implement the principles of management as stipulated in Government Regulation Number 11 of 2021. This community service aims to optimize the role of VOE by providing a legal understanding of the implementation of Taman Jaya VOE governance in order to improve the economy of Taman Village. The service is carried out through socialization, by the method of presenting legislative materials which is the basis for managing VOE to managers, village officials, and the community as the target of the activity. Accordingly, the results of this community service activity, the principles of VOE management that has been regulated in laws and regulations be able to implemented properly.